Neuroaudiological Considerations for the Auditory Brainstem Response and Middle Latency Response Revisited: Back to the Future - Musiek, Frank E.; Baran, Jane A. (Seminars in Hearing, 2022)
The auditory brainstem response (ABR) and middle latency response (MLR) are two sets of evoked potentials that have made major contributions to the field of diagnostic audiology. Many of these contributions were guided by clinical research audiologists. Though many of these auditory evoked potentials (AEPs) are still being used diagnostically by audiologists, there has been a steep decline in their popularity both clinically and in the research laboratory. This is indeed most unfortunate because these AEPs could and should be advancing our field and benefitting many patients. In this article, some critical research is overviewed that addresses some of the reasons why these AEPs (ABR and MLR) are not being utilized as frequently as they should be for neuroauditory assessments. Reflecting on our past when ABR and MLR were more commonly used can serve as a model for our future. Multiple applications and the diagnostic value of these AEPs are presented in an effort to convince audiologists that these electrophysiologic procedures should be revisited and reapplied in the clinic and research settings. It is argued that the dwindling use of ABR and MLR (and AEPs in general) in the field of audiology is not only remarkably premature but also lacks good scientific grounding. While on the other hand, if applied clinically, the value of these AEPs is both substantial and promising.
Keywords: Auditory Brainstem Response; middle latency response; vestibular schwannomas; magnetic resonance imaging; neuroaudiology